Determination of the threshold of nanoparticle behavior: Structural and electronic properties study of nano-sized copper - Torres-Vega J.J. (2014)
In the present work we determine the threshold of the nanoparticle behavior of copper nanoparticles by studying their structural and electronic properties. The studied nanoparticles contain from 13 to 8217 atoms and were obtained by molecular dynamics simulations using the Johnson potential for copper based on the embedded atom method. The results indicate that for small copper nanoparticles (o1000 atoms, 2.8 nm) the surface plays an important role in their physical properties. Whereas, for large nanoparticles (42000 atoms, 3.5 nm), with spherical-like external shape and large percentage of fcc-like local structure, this effect is negligible and their electronic character are similar to such expected in solid copper. Finally, it has also been shown that copper nanoparticles change their electronic character, from metallic to insulating, after increasing the strength of the chemical disorder.